2019
DOI: 10.1111/fcp.12463
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo‐oxygenase selectivity and chemical groups of nonsteroidal anti‐inflammatory drugs and the frequency of reporting hypersensitivity reactions: a case/noncase study in VigiBase

Abstract: To date, no reports of hypersensitivity reactions (HSRs) among nonsteroidal anti‐inflammatory drugs (NSAIDs) according to cyclo‐oxygenase (COX) selectivity and chemical groups have been published in a single study. The present study assessed the reporting frequency of HSRs for NSAIDs based on their relative inhibitory potency toward COX enzymes and chemical groups, including the presence/absence of a functional sulfonamide group, in strata observed 5 years after market authorization. A case/noncase study was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…On the other hand, thromboxane is a potent vasoconstrictor. Inhibition of thromboxane decreases the likelihood of occluded blood vessels, lowering the possibility of ischemic stroke ( 40 , 46 50 ). Previous published studies proposed different hypotheses that due to the selectivity of COX-2 inhibitors, they do not affect thromboxane production due to its primary synthesis in platelets which only express COX-1 and therefore continue vasoconstriction ( 8 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, thromboxane is a potent vasoconstrictor. Inhibition of thromboxane decreases the likelihood of occluded blood vessels, lowering the possibility of ischemic stroke ( 40 , 46 50 ). Previous published studies proposed different hypotheses that due to the selectivity of COX-2 inhibitors, they do not affect thromboxane production due to its primary synthesis in platelets which only express COX-1 and therefore continue vasoconstriction ( 8 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the drugs that are commonly involved in cross‐reactive hypersensitivity are predominantly COX‐1 inhibitors (Antman, DeMets, & Loscalzo, 2005; Ayuso et al, 2014; Cryer & Feldman, 1998; Pierre et al, 2007). COX selectivity is related to the presentation of cross‐reactive NSAID hypersensitivity, with COX‐1 inhibitors being commonly involved in these reactions (Bakhriansyah, Meyboom, Souverein, de Boer, & Klungel, 2019), whereas COX‐2 specific inhibitors are well tolerated in patients with cross‐reactive NSAID hypersensitivity (Weberschock, Muller, Boehncke, & Boehncke, 2007), in agreement with the low frequency of cases related to COX‐2 inhibitors in this study (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the presence of selective COX‐2 inhibitors as triggering drugs was marginal (about 1% of patients), thus supporting the hypothesis of COX‐1 inhibition as the main mechanism involved in cross‐reactive NSAID hypersensitivity (Cahill & Boyce, 2017; Dona et al, 2018, 2019; Kowalski, Borowiec, Kurowski, & Pawliczak, 2007; Li & Laidlaw, 2019; Mastalerz et al, 2019). This hypothesis was further reinforced in a study involving more than 13,000 cases with NSAID‐related hypersensitivity reactions, reporting that NSAIDs with a poor COX‐selectivity, in opposition to COX‐2 selective inhibitors, are the more commonly involved of hypersensitivity reactions (Bakhriansyah, Meyboom, Souverein, de Boer, & Klungel, 2019; Morales et al, 2014).…”
Section: Introductionmentioning
confidence: 97%
“…The role of COX-1 inhibition in the etiopathogenesis of crosshypersensitivity to NSAIDs has been the object of controversy for years (Kowalski et al, 2007;Doña et al, 2018;Mastalerz et al, 2019). Supporting this hypothesis, it has been shown that COX-2 inhibitors are well tolerated among patients with crosshypersensitivity to NSAIDs (Morales et al, 2014;Bakhriansyah et al, 2019) and that patients with PTGS1 gene variants related to a decreased activity (Agúndez et al, 2014;Agúndez et al, 2015b;Lucena et al, 2019) are at increased risk of developing crosshypersensitivity to NSAIDs (García-Martín et al, 2021). Interestingly, preliminary evidence suggests that crosshypersensitivity to NSAIDs is dose-dependent (Palmer, 2005;Kong et al, 2007;Kowalski et al, 2013;Blumenthal et al, 2017) and, therefore, it could be speculated that individuals with impaired NSAID clearance (and therefore increased drug exposure) might have increased risk of developing cross-hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…According to their clinical presentation, cross-hypersensitivity reactions could be classified as NSAIDs-exacerbated respiratory disease (NERD), NSAIDs-exacerbated cutaneous disease (NECD), and NSAID-induced urticaria/angioedema (NIUA) ( Kowalski et al, 2013 ). These non-immunological reactions are believed to be originated via inhibition of cyclooxygenase 1 (COX-1) enzyme and the release of histamine and sulphidopeptide leukotrienes ( Kowalski et al, 2007 ; Doña et al, 2018 ; Bakhriansyah et al, 2019 ; Li and Laidlaw, 2019 ; Mastalerz et al, 2019 ). In this context, it is important to bear in mind that NSAIDs antagonize inflammation by interfering with the function of cyclooxygenases, and therefore their association with nonallergic hypersensitivity might be related to disequilibrium in the arachidonic acid degradation pathways, that is, interference with the formation of prostaglandins and thromboxanes, thus resulting in the shunting of arachidonic acid metabolism towards the 5-lipoxygenase pathway, and the consequent increase in the release of cysteinyl leukotrienes ( Sánchez-Borges, 2010 ; Caimmi et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%